The BBC and national identity in Britain, 1922-53. - Hajkowski, Thomas (Studies in Popular Culture., 2010)
Examining the ways in which the BBC constructed and disseminated British national identity during the second quarter of the twentieth century, this book is the first study that focuses in a comprehensive way on how the BBC, through its radio programs, tried to represent what it meant to be British. The BBC and national identity in Britain offers a revision of histories of regional broadcasting in Britain that interpret it as a form of cultural imperialism. The regional organization of the BBC, and the news and creative programming designed specifically for regional listeners, reinforced the cu.